Study of Numerical Simulation during ECAP Processing of Can Based on Smooth Particle Hydrodynamics. (22nd May 2019) - Niu, Xiaofeng; Wang, Chenchen; Chan, K. C.; Wang, Han; Feng, Shidong
Abstract : ECAP (Equal Channel Angular Pressing) is a well-known technique by which a specimen is pressed into an ECAP die to improve the mechanical properties by the nearly pure shear during the deformation process. In the ECAP processing of can, the specimen is canned with a protection material layer to avoid the cracking during deformation. At present, most simulation studies of ECAP are conducted based on the finite element method, in which large deformation can cause serious mesh distortion, resulting in a decrease of the simulation accuracy. In this study, based on SPH (Smooth Particle Hydrodynamics), we utilize the invalid particles and crack treatment techniques, building an ECAP mathematical model incorporating damage prediction, in order to simulate crack initiation and dynamic extension in the ECAP process. In simulation of pure magnesium during ECAP at room temperature using industrial pure iron as the canned material, the simulation results based on SPH method show that the plastic deformation of the pure magnesium specimen is homogeneous in both the vertical direction and the extrusion direction. The average equivalent strain value of the specimen in the major deformation area is 1.31, which is similar to the finite element simulation result in which the average equivalent strain value of the major deformation area is 1.24. From the damage perspective, the maximum damage values of the inside specimen obtained by the SPH method and the finite element method are both less than 0.16, with both values being far lower than the critical fracture accumulated damage value. The test results well match the simulation results.